2019
DOI: 10.1186/s12864-019-5517-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation of Sclerotinia sclerotiorum during infection of Glycine max: on the road to pathogenesis

Abstract: Background Sclerotinia sclerotiorum is a broad-host range necrotrophic pathogen which is the causative agent of Sclerotinia stem rot (SSR), and a major disease of soybean ( Glycine max ). A time course transcriptomic analysis was performed in both compatible and incompatible soybean lines to identify pathogenicity and developmental factors utilized by S. sclerotiorum to achieve pathogenic success. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 116 publications
(201 reference statements)
16
42
0
Order By: Relevance
“…Many of these enzymes were up-regulated in the current study ( Table 2). Consistent with our findings, previous comparative transcriptome analyses [19,[28][29][30][34][35][36] have reported that a large number of cell wall-degrading enzymes were up-regulated during pathogenesis, while at least…”
Section: Cwde and Proteolytic Enzymessupporting
confidence: 92%
See 4 more Smart Citations
“…Many of these enzymes were up-regulated in the current study ( Table 2). Consistent with our findings, previous comparative transcriptome analyses [19,[28][29][30][34][35][36] have reported that a large number of cell wall-degrading enzymes were up-regulated during pathogenesis, while at least…”
Section: Cwde and Proteolytic Enzymessupporting
confidence: 92%
“…In contrast, Sslacc2 (sscle_03g023030) was consistently up-regulated (35-40 fold-change, l2fc 5.13-5.34) at both time points (Table 3). A similar expression pattern was observed in soybean-S. sclerotiorum interaction by Westrick et al [34]. In B. cinerea, laccase gene BcLCC2, along with BcAtrB, an ABC transporter, was required for detoxification of the antifungal phenolic antibiotic 2,4-diacetylphloroglucinol [57].…”
Section: Detoxification Of Xenobiotic Compoundssupporting
confidence: 79%
See 3 more Smart Citations